Pluriannual Plan (PPA) containing Macro-Strategic Density in Municipal Public Management: description and analysis of a PPA's elaboration process in the municipality of Osasco, Brazil (2018-2021) - Rodrigues Nascimento, Ingrid Cristine; Coelho, Fernando de Souza; Bono Olenscki, Antonio Roberto [UNESP]; Pereira da Silva, Raphael Borella (Univ Federal Paraiba, 2020)
Goal: Brazilian literature on strategic planning in the public sector has shown how the Pluriannual Plan (PPA) instrument in local governments remains - recurrently - structured from a purely technical-budgetary perspective, or merely as a legal obligation, with little evidence of its potential strategic use in municipal public management. This article sheds light on this subject, considering and employing the concept of macro-strategic density and applying it to the case study of the 2018-2021 Pluriannual Plan's formulation in the municipality of Osasco, Brazil. Methodology: this is an exploratory research that used the case study method with the triangulation of data / information from document analysis, semi-structured interviews with key informants and participant observation (in 2017) of the process by one of the authors of this present study. Result: the article describes how the municipality prepared the government planning and analyzes whether this process corresponded to the principles of macro-strategic density, indicating, as a result, the characterization of a Strategic PPA. Contribution: the paper contributes to the national literature in na empirical sense, once it identifies the raise and development of a Strategic-oriented PPA in a local public management, something unusual in the country's municipalities.
Keywords: Government Planning; Pluriannual Plan; Strategy; Municipal Government